2023
DOI: 10.3390/pathogens12020282
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Immunological Response against Trypanosoma cruzi

Abstract: Chagas disease is a chronic systemic infection transmitted by Trypanosoma cruzi. Its life cycle consists of different stages in vector insects and host mammals. Trypanosoma cruzi strains cause different clinical manifestations of Chagas disease alongside geographic differences in morbidity and mortality. Natural killer cells provide the cytokine interferon-gamma in the initial phases of T. cruzi infection. Phagocytes secrete cytokines that promote inflammation and activation of other cells involved in defence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 128 publications
0
15
0
Order By: Relevance
“…Toll-like receptors play an important role in the elimination of microbes through recognition of pathogen-associated patterns and induction of inflammatory cytokines and type I interferons ( Fitzgerald and Kagan, 2020 ; Motomura et al, 2023 ). T. cruzi molecules such as surface glycoinositolphospholipids (GPIs) and parasite DNA/RNA sequences can be sensed by TLRs ( Macaluso et al, 2023 ). In fact, several investigators have shown the significance and involvement of TLRs in the control of T. cruzi infection ( Caetano et al, 2011 ; Castillo et al, 2017b ; Queiroga et al, 2021 ; Ait Djebbara et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Toll-like receptors play an important role in the elimination of microbes through recognition of pathogen-associated patterns and induction of inflammatory cytokines and type I interferons ( Fitzgerald and Kagan, 2020 ; Motomura et al, 2023 ). T. cruzi molecules such as surface glycoinositolphospholipids (GPIs) and parasite DNA/RNA sequences can be sensed by TLRs ( Macaluso et al, 2023 ). In fact, several investigators have shown the significance and involvement of TLRs in the control of T. cruzi infection ( Caetano et al, 2011 ; Castillo et al, 2017b ; Queiroga et al, 2021 ; Ait Djebbara et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…This review supports existing literature findings, indicating that patients with CD4+ T-cell counts below 200 cells per mm 3 were associated with more severe CNS Chagas disease (Córdova et al ., 2013; Pittella, 2013). As the immune system relies on CD4+ T helper 1 (Th1) cells for protective immunity during the acute and chronic stages of Chagas disease, it is reasonable to expect higher parasitaemia and poor disease control in immunocompromised patients (Brener and Gazzinelli, 1997; Macaluso et al ., 2023). T-cell responses, mediated by both CD4+ and CD8+ T cells, in Chagas disease are rather complex.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 7 million individuals are infected worldwide, causing approximately 12 thousand deaths annually ( 1 , 2 ). While most patients affected by T. cruzi are asymptomatic, about 30% of infected individuals develop Chronic Chagas Cardiomyopathy (CCC) ( 3 , 4 ), which is recognized as the most critical clinical manifestation of the disease ( 5 , 6 ). Patients with CCC exhibit electrocardiographic changes that can lead to severe arrhythmias, heart failure, and thromboembolic phenomena.…”
Section: Introductionmentioning
confidence: 99%